Budgeting for comprehensive sexual and reproductive health and rights under universal health coverage. Issue 2 (17th December 2020) - Lince-Deroche, Naomi; Sully, Elizabeth A; Firestein, Lauren; Riley, Taylor
Abstract: Achieving universal health coverage (UHC) for sexual and reproductive health (SRH) requires informed budgeting that is aligned with UHC objectives. We draw data from Adding It Up 2019 (AIU-2019) to provide critical new country-level and regional, intervention-specific costs for the provision of SRH services. AIU-2019 is a cost-outcomes analysis, undertaken from the health system perspective, which estimates the costs and impacts of offering SRH care in low- and middle-income countries. We present direct cost estimates for 109 SRH interventions and find that human resources comprise the largest category of direct SRH service costs and that the most expensive services in the model are largely preventable. We use scenario analysis to explore the synergistic costs and impacts of providing SRH interventions in clusters, focussing on chlamydia and gonorrhoea treatment, provision of safe abortion and post-abortion care services, and safe childbirth services. When costs are considered for the preventive and impacted services in these three clusters, there are cost savings for some of the impacted services in the packages and for the abortion-related package overall. The direct cost estimates from our analysis can be used to guide UHC budgeting and planning efforts. Having these cost estimates and understanding the potential for cost savings when providing comprehensive SRH services are critical for efforts to fulfil the rights and needs of all individuals, including the most marginalised, to access this essential care.